Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Pekerjaan Umum Penataan Ruang Dan Pertanahan Ciamis - Lutfi Noor Apriliani; Arga Sutrisna; Ai Kusmiati Asyiah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
The purpose of this study was to determine the effect of workload and work environment on the performance of employees of the Ciamis Spatial Planning and Land Public Works Office. The research method used is a quantitative method of 55 respondents who are employees of the Ciamis Spatial Planning and Land Public Works Office. The type of data used is primary data obtained through distributing questionnaires to respondents and secondary data. Testing the data in this study includes validity test, reliability test, and classical assumption test. The data analysis tool used is multiple linear regression, correlation coefficient, and determination coefficient using IBM SPSS (Statitical Product and Service Solution) Windows version 25 software. Based on the results of the study it can be seen that workload and work environment simultaneously have a positive and significant effect on employee performance Ciamis Spatial Planning and Land Public Works Office. Workload partially has a positive and significant effect on the performance of employees of the Ciamis Spatial Planning and Land Public Works Office. The work environment partially has a positive and significant effect on the performance of employees of the Ciamis Spatial Planning and Land Public Works Office.